2012
DOI: 10.1088/0004-637x/756/2/171
|View full text |Cite
|
Sign up to set email alerts
|

A HUBBLE SPACE TELESCOPE SURVEY OF H2 EMISSION IN THE CIRCUMSTELLAR ENVIRONMENTS OF YOUNG STARS*

Abstract: The formation timescale and final architecture of exoplanetary systems are closely related to the properties of the molecular disks from which they form. Observations of the spatial distribution and lifetime of the molecular gas at planet-forming radii (a < 10 AU) are important for understanding the formation and evolution of exoplanetary systems. Toward this end, we present the largest spectrally resolved survey of H2 emission around low-mass pre-main-sequence stars compiled to date. We use a combination o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
202
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 108 publications
(213 citation statements)
references
References 136 publications
9
202
1
Order By: Relevance
“…We measured the metal emission lines by employing a Gaussian line-fitting code that takes into account the linespread function of the instrument used to create that portion of the spectrum. For instance, the N Vand C IVlines are fit with a single-component Gaussian emission line convolved with the appropriate wavelength-dependent HST-COS line-spread function 21 (France et al 2012b). Some emission lines are clearly better described by a two-component model (Wood et al 1997), but this only applies to a small number of emission lines in the sample and we assume a single Gaussian for the results presented in this paper.…”
Section: Results: 5 å To 5 μM Irradiance Spectramentioning
confidence: 99%
“…We measured the metal emission lines by employing a Gaussian line-fitting code that takes into account the linespread function of the instrument used to create that portion of the spectrum. For instance, the N Vand C IVlines are fit with a single-component Gaussian emission line convolved with the appropriate wavelength-dependent HST-COS line-spread function 21 (France et al 2012b). Some emission lines are clearly better described by a two-component model (Wood et al 1997), but this only applies to a small number of emission lines in the sample and we assume a single Gaussian for the results presented in this paper.…”
Section: Results: 5 å To 5 μM Irradiance Spectramentioning
confidence: 99%
“…Our X-shooter data are taken well into the second dimming event. Since RW Aur A has been spectrally monitored at different wavelengths in the past decade, in particular in the optical (Alencar et al 2005;Chou et al 2013;Petrov et al 2015;Takami et al 2016) and in the UV (France et al 2012(France et al , 2014McJunkin et al 2013 The solid vertical lines show the dates when the UVES and X-shooter (black) spectra were taken (colour legend for UVES spectra is in Table 1). The dashed vertical lines show the dates of the four optical spectra by Chou et al (2013), which overlap on the used scale.…”
Section: Resultsmentioning
confidence: 99%
“…The dashed vertical lines show the dates of the four optical spectra by Chou et al (2013), which overlap on the used scale. The brown and grey dashed-dotted lines show the dates of the two UV HST spectra by France et al (2012France et al ( , 2014. Right panel: same as in left panel, zoomed during the second dimming event.…”
Section: Resultsmentioning
confidence: 99%
“…For N V, we load the 1237.1 -1243.9Å spectra into the multi-Gaussian fitting routine described in France et al (2012b) and fit all of the observed features with Gaussian emission lines convolved with the appropriate wavelength dependent HST +COS line-spread function (Kriss 2011) 11 . Emission lines with FWHM < 100 km s −1 and within ± 40 km s −1 of the rest wavelength of a known H 2 emission line pumped by Lyα [B -X (2 -2)R(11) λ1237.54Å, B -X (1 -2)P (8) λ1237.87Å, and C -X (1 -5)R(9) λ1240.87Å] were then subtracted from the data.…”
Section: Hot Gas Emission Lines and Subtraction Of H 2 Fluorescent Emmentioning
confidence: 99%